1985
DOI: 10.1046/j.1537-2995.1985.25285169198.x
|View full text |Cite
|
Sign up to set email alerts
|

Red cell alloantibodies in thalassemia major

Abstract: Clinical and serological data on 1435 Italian thalassemia major patients were collected during a cooperative study involving 19 centers in 10 regions. The main findings were as follows: 18 percent of the patients were under 6 years of age, 63 percent between 6 and 15, and 19 percent over 15. Forty-one percent had undergone splenectomy. Sixty-two percent of the patients were maintained at pretransfusion hemoglobin levels higher than 10 g per dl, 36 percent between 8 and 10 g per dl, and 2 percent below 8 g per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
81
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 7 publications
11
81
2
Order By: Relevance
“…In most reports from Western countries, RBC antibodies most commonly associated with alloimmunization in thalassaemia are directed against C, E and Kell antigens [6, 11,12]. Anti-D alloantibodies are also frequently reported even though most patients receive RBC products crossmatched for ABO and RhD blood groups worldwide.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In most reports from Western countries, RBC antibodies most commonly associated with alloimmunization in thalassaemia are directed against C, E and Kell antigens [6, 11,12]. Anti-D alloantibodies are also frequently reported even though most patients receive RBC products crossmatched for ABO and RhD blood groups worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…The relative homogeneity of donor and recipient populations in Greece and Italy has been shown to contribute to lower alloimmunization rates for transfused patients with thalassaemia [11,12] compared to more heterogeneous populations in other countries, such as Kuwait [19] and Taiwan [14]. One study from USA reported an alloimmunization rate of 20.8 % in Asians patients with thalassaemia where only 5 % of local blood donors were Asian [5].…”
Section: Rbc Antigenic Differences Between Blood Donor and Recipientmentioning
confidence: 99%
See 1 more Smart Citation
“…Various centers all around the world have reported different frequencies of alloimmunization. The frequency of red cell alloimmunization ranging from 3.1 to 30 % [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The some of these reports have a high rate of alloimmunization [2,6,8,15] but majority of centers have reported low rate of alloimmunization [3, 12, 13, 16-18, 20, 21].…”
Section: Discussionmentioning
confidence: 99%
“…Some alloantibodies are hemolytic and may cause hemolytic transfusion reactions and limit the availability of further safe transfusion [2]. The most frequent detected antibodies are directed against Rhesus (Rh), Kell (K), Duffy (Fy), Kidd (Jk) system antigens, in order of frequency [3]. The reported incidence of alloimmunization in multiply transfused thalassemics patients was 3-30 % [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%